Pan-Cancer Analysis of the Oncogenic and Immunological Role of Solute Carrier Family 6 Member 8 (SLC6A8) - Yang, Xin; Li, Qiao (Frontiers in Genetics, 2022)
There is mounting evidence on the implication of SLC6A8 in the initiation and progression of human cancers. However, a comprehensive understanding of the role of SLC6A8 in pan-cancer remains elusive yet. Bioinformatics analysis was performed to investigate the expression and mutation profiles of SLC6A8 in cancers, and the association of SLC6A8 expression with cancer patients’ survival and immune cell infiltration. In general, SLC6A8 is significantly upregulated across multiple cancers. SLC6A8 expression was inconsistently prognostic in different types of cancer, albeit associated with favorable survival in the vast majority of cancers. The receiver operating characteristic curves showed that SLC6A8 was relatively accurate in identifying possible cancer patients. The genetic alteration of SLC6A8, including mutation, amplification and deletion, was frequently present across various types of cancer. Mechanistically, SLC6A8 might be involved in tumorigenesis through “carbon metabolism” and “HIF-1 signaling pathway”. Besides, SLC6A8 expression had significant correlation with immune checkpoints genes and tumor-infiltrating immune cell abundances. The present study offers a novel insight into the roles of SLC6A8 in the oncogenesis and development of multiple common cancers.